Calculus Problem Solving: A Review of Krulick and Rudnick’s Theory for First Year Engineering Students. - Joko Suprayitno, Iswahyudi; Aziz, Abdul (Education, Science, and Technology International Conference, 2026)
ABSTRACT The purpose of this study is to determine the initial ability of Engineering students in working on calculus problems seen from the perspective of Krulick And Rudnick’s theory. The research method used is descriptive qualitative involving 151 mechanical engineering students at one of the universities in the city of Semarang. Based on these 151 students, they are classified into several sections focused on the aspects of Read And Think; Explore And Plan; Select A Strategy; Find And Answer, Reflect And Extend. Based on these aspects, there are fundamental weaknesses in the aspects of Explore And Plan; Select A Strategy; Find And Answer, Reflect And Extend. For teachers of calculus material, it is necessary to pay attention to the theoretical aspects of Krulick And Rudnick starting from the explore and plan stage to the reflect and extend aspect. Keywords: problem solving, krulick rudnick theory, calculus.